1998
DOI: 10.1021/ja973669n
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Neurobiology Implications from Fabrication and Analysis of Hippocampal Neuronal Networks on Patterned Silane-Modified Surfaces

Abstract: We have determined the parameters necessary to fabricate reproducible neuronal patterns which we are using to begin studying fundamental issues in developmental neurobiology. The addition of a beam homogenizer, as well as a new surface preparation, has enabled the routine production of reproducible, high-resolution (2−20 μm) organosilane patterns. The effects of surface preparation and beam dosage were monitored using X-ray photoelectron spectroscopy (XPS) and proof of patterning is provided by high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
138
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(153 citation statements)
references
References 53 publications
13
138
2
Order By: Relevance
“…The quality of the surfaces was in agreement with previously reported results. 32,46,47 Palladium-Catalyzed Metallization of Patterned Silane Monolayers. Patterned samples were visualized using a palladium-catalyzed copper reduction reaction, modified from Kind et al 48 In this reaction, copper is deposited in regions containing the amine terminated silane DETA.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The quality of the surfaces was in agreement with previously reported results. 32,46,47 Palladium-Catalyzed Metallization of Patterned Silane Monolayers. Patterned samples were visualized using a palladium-catalyzed copper reduction reaction, modified from Kind et al 48 In this reaction, copper is deposited in regions containing the amine terminated silane DETA.…”
Section: ■ Discussionmentioning
confidence: 99%
“…[53] It has also been demonstrated by Wheeler and co-workers that patterned neurons synapse with each other, release neurotransmitters and develop electrical activity. [54][55][56] Furthermore, restricting neurons to patterns has been shown to enhance the cellular activity such as glutamine secretion and electrical activity as compared to random monocultures of neurons. [57,58] …”
Section: Patterned Versus Random Co-culturementioning
confidence: 99%
“…22| Use XPS to characterize the monolayer of DETA by monitoring the N 1s peak 9,13 . ' PAUSE POINT Samples should be stored in dessicator before use.…”
Section: |mentioning
confidence: 99%
“…First, a unique chemically defined serum-free medium supplemented with specific growth factors was developed to study the muscle differentiation process. Second, a synthetic, nonbiological, patternable 8,9 , cell growth promoting substrate, N-1 [3(trimethoxysilyl)propyl] diethylenetriamine (DETA), coated on glass coverslips [10][11][12] , was used as a template to grow the skeletal muscle cells. Third, it was demonstrated that when the dissociated muscle cells were plated on fabricated microcantilevers, they aligned along the long axis of the cantilever to form aligned myotubes.…”
Section: Introductionmentioning
confidence: 99%